An exploratory study of students with dyslexia in a mixed online and on-campus environment at an Australian regional university. Issue 2 (3rd July 2021) - Maurer-Smolder, Christina; Hunt, Susan; Parker, Shane Bruce
ABSTRACT: Research suggests that tertiary students with dyslexia are less likely to achieve high or passing marks in their studies than students without dyslexia. The aim of this investigation was to discover the nature of barriers faced by students with dyslexia at an Australian regional university where two thirds of the overall population had a distance component to their study. First, a validated survey was used to recruit students for interview. Second, a varied sample of twelve students was selected for participation in hour-long semi-structured interviews. Themes that emerged from the data are related to time and effort, videos and lectures, skills and assessment and services and adjustments. Findings of the study underscore the need for educators to rethink the effectiveness of traditional models for supporting students with dyslexia. Implications toward more inclusive practice in the teaching of university students with dyslexia in a mixed online and on-campus environment are discussed.